A Study on Leveraging Library Infrastructure for Entrepreneurial Development - Deryane Imalinda; Bayti Nur; Sufnirayanti Sufnirayanti; Putra Agriend S.; Liang Rendy (BIO Web of Conferences)
The concept of entrepreneurship has undergone a significant narrowing of meaning. If in the past, entrepreneurs were synonymous with business people who had assets, turnover, and measurable business strategies, now entrepreneurs can refer to small traders. Home-based businesses, micro, small, and medium enterprises that should have a good entrepreneurial concept have now largely forgotten the important aspects of entrepreneurship. The low interest in entrepreneurship has an impact on the lack of development of surrounding UMKM. UMKM that have been established but require further development are a great potential in the local economy. With the existing foundation, strategic steps can be taken to improve the quality, competitiveness, and scale of these UMKM. The paradigm shift has taken libraries beyond their function as places to store books. Now, libraries serve as comprehensive resource centers, including for businesses that need access to information and supportive workspaces. As centers of information and innovation, libraries are now playing an active role in supporting local economic growth, especially by providing the facilities and services needed by businesses. This research focuses on the utilization of library facilities that can be accessed and utilized by entrepreneurs, thereby increasing the interest in genuine entrepreneurship by fulfilling the important aspects of entrepreneurship.